Bharavahaka pillar bracket - Temples of India Project Team (Jio Institute, 2024)
A fragment of a heavy pillar is placed near the frontal entry point. The fragment is a pillar bracket which depicts four bharavahakas (load bearers) on each side. These bharavahakas are four-armed and adorned with beautiful jewelleries.